Bottom-up fabrication of FeSb2 nanowires on crystalline GaAs substrates with ion-induced pre-patterning - Weinert, Tom; Hübner, René; Facsko, Stefan; Erb, Denise J. (Frontiers in Physics, 2023)
In recent decades, nanostructuring has become one of the most important techniques to design and engineer functional materials. The properties of nanostructured materials are influenced by the interplay of its instrinsic bulk properties and the properties of its surface - the relative importance of the latter being enhanced by the increased surface-to-volume ratio in nanostructures. For instance, nanostructuring of a thermoelectric material can reduce the thermal conductivity while maintaining constant electrical conductivity and the Seebeck coefficient, which would improve the thermoelectric properties. For that reason, this study investigated the possibility of preparing nanowires of iron antimonide (FeSb2), a thermoelectric material, on single-crystalline gallium arsenide GaAs (001) substrates with ion-induced surface nanoscale pre-patterning and characterized the structure of the prepared FeSb2 nanowires. The GaAs (001) substrates were pre-patterned using 1 keV Ar+ ion irradiation. By using an ion source with a broad, unfocused ion beam at normal incidence, the patterned area can be scaled to nearly any size. The self-organized surface morphology is formed by reverse epitaxy and is characterized by almost perfectly parallel-aligned ripples at the nanometer scale. For the fabrication of FeSb2 nanowires, iron and antimony were successively deposited on the pre-patterned GaAs substrates at grazing incidence and then annealed. They were characterized using transmission electron microscopy (TEM), in particular high-resolution TEM imaging for structure analysis and spectrum imaging analysis based on energy-dispersive X-ray spectroscopy for element characterization. With the presented fabrication method, FeSb2 nanowires were produced successfully on GaAs(001) substrates with an ion-induced nanopatterned surface. The nanowires have a polycristalline structure and a cross-sectional area which is scalable up to 22 × 22 nm2. Due to the high order nanostructures on the GaAs substrate, the nanowires have a length of several micrometer. This bottom-up nanofabrication process based on ion-induced patterning can be a viable alternative to top-down procedures regarding to efficiency and costs.